Millennium Development Goals (MDG) Gap Task Force Report 2012 - United Nations (United Nations, 2013)
The 2012 Report will continue to follow the progress on official development assistance, market access, debt sustainability, access to essential medicines and new technologies as prescribed by the Millennium Development Goal 8. Closer attention will be given to the impact of the global crisis on meeting the targets, and ways to further increase aid effectiveness following the recommendations of the Fourth High Level Forum on Aid Effectiveness. Some evidence on whether the needs of developing countries are being met will be presented. The Report will also serve as a building block to start formulating the post-2015 development agenda by taking stock of the progress made so far.